MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Sri Suharti; Eko Suncaka; Sri Fatmawati (UNISAN JURNAL, 2025)
This research aims to find out and analyze the management of facilities and infrastructure in improving the quality of learning. This type of research is qualitative research. Data collection was carried out by conducting observations, interviews and documentation. After the data is collected and analyzed qualitatively, the data is processed by data reduction, presentation and drawing conclusions. The results of the research show that facilities and infrastructure can improve the quality of learning, if the infrastructure is good and of high quality then the learning will be of quality, without facilities and infrastructure the learning process will not be of quality. One of the infrastructure in learning is the existence of good school buildings, classrooms. comfortable, adequate learning media, good places to worship, good learning methods used by teachers, and good places for extracurricular activities. All these infrastructure facilities will improve the quality of learning